THE ENVIRONMENT REPRESENTATIONS IN CONTEMPORARY ARAB ART FROM THE RURAL TO THE URBAN - Al-Abbas, Mohammed Baker M (PEOPLE: International Journal of Social Sciences, 2016)
This article located three artists from three different Arab countries, who represented environment by producing different art production. They portrayed, installed, and composed images that belong to rural or urban environments where they selected landscapes that represent certain places. They portrayed certain objects that symbolize rural or urban environments. The investigated artworks are made by artists who had different collective and cultural backgrounds as well as different social realities. Therefore, this article investigates the concepts of representing places and environments in the Arab Contemporary Arts, where the artists analysed and installed the urban and rural images in their current social situations. The images as well as the belongings of the Arab contemporary urban and rural places appear in visual arts strongly through different forms of art such as installation art, abstraction, realism, or semi-realism; those artworks can be viewed in galleries, art fairs, and biennales.